HUBUNGAN AKTIVITAS FISIK HARIAN DENGAN KEJADIAN DISMENOREA PADA REMAJA SISWI KELAS VIII SMPN 3 PONOROGO - Yani Fidi Astuti; Siti Munawaroh; Sugeng Mashudi; Laily Isro'in; Saiful Nurhidayat (Health Sciences Journal, 2022)
Menstruation is an important part of a woman. Menstrual disorders are often felt by some young women. The most common disorder is dysmenorrhea. One of the factors that cause dysmenorrhea is physical activity. This study aims to determine the relationship between daily physical activity and the incidence of dysmenorrhea in adolescent girls.The design of this research is correlation with cross sectional approach. The population in this study was class VIII students at SMPN 3 Ponorogo with a sample size of 33 respondents. In this study using purposive sampling.Technical data collection using a questionnaire and analysis using Fisher exact with a significant 0.05. The results of the study of daily physical activity found that most of the 17 respondents (51.5%) were in the light category. And as many as 16 respondents (48.5%) with moderate category physical activity. In the incidence of dysmenorrhea in adolescents as many as 26 respondents (78.8%) experienced dysmenorrhea. Analysis of the relationship obtained p value (0.398) (0.05) which means H0 is accepted and H1 is rejected, which means there is no relationship between physical activity and the incidence of dysmenorrhea in adolescents.The results showed that most of the adolescents who experienced dysmenorrhea were expected to increase physical activity and exercise regularly in order to prevent the occurrence of dysmenorrhea.